KEAWETAN PAPAN PARTIKEL DARI BATANG KELAPA SAWIT (Elaeis guineensis Jacq) DENGAN TAMBAHAN ASAP CAIR TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) Durability of Particleboard from Oil Palm Trunk (Elaeis guineensis Jacq) with Addition Liquid S - narti, Su; Setyawati, Dina; haida, Nur; Diba, Farah (Universitas Tanjungpura, 2014)
The study aims to determine the effect of the concentration of liquid smoke from oil palm empty fruit bunches on the durability of oil palm trunk particleboard (Elaeis guineensis Jacq) and to determine the optimum concentration of liquid smoke. The method of research is an experiment carried out in completely randomized design (CRD), which consists of three treatments and three replications. Particle board made with three types of layers, with the size of 30 cm x 30 cm x 1 cm, the target density of 0.8 g / cm3, compression temperature 140oC, pressure of 25 kg / cm2 for 10 minutes. Adhesive used is Urea Formaldehyde with a concentration of 16% for the surface layer (face) and bottom (back) and 14% for the middle layer (core) with a solid content 52%. The treatment used is liquid smoke with concentration 0%, 5% and 10%. Testing the durability of particle board using baiting methods to subterranean termite Coptotermes curvignathus Holmgren for 21 days. The results of research showed that the oil palm trunk particleboard with liquid smoke concentration level of 10% was the best 2 vality the mortality value 100%. Meanwhile the best result for particleboard weight loss was achived on liquid smoke level 5% with average value 0.45% from physical, mechanical and durability properties of particleboard made from oil palm with liquid smoke, the best result was achieved on particleboard with level 10%. Key words: Urea formaldehyde, liquid smoke, Coptotermes curvignathus Holmgren, durability particleboard